Effect of Composition and Duration of Media Fermentation on Components and Yield of Merang Mushrooms (Volvariella volvacea) - Hanafi, Harri; Ria, Elly Roosma; Komariah, Ai; Sondari, Nunung (Breeding Science Society of Indonesia (BSSI) / PERIPI, 2024)
In the cultivation process, the composition of growing media and the length of composting of growing media affect the yield of merang mushrooms. This research was conducted in June 2023. Aiming, to determine the effect of the interaction of composition and duration of media composting on the components of yield and yield of mushroom. This research was conducted in the mushroom experiment barn of the Faculty of Agriculture, Winaya Mukti University, with an altitude of 898 meters above sea level. Using a randomised group design (RAK) factorial pattern, consisting of two factors. The first factor is media composition. m1 (100% cotton + 0% rice husk), m2 (75% cotton+25% rice husk), m3 (50% cotton+50% rice husk), m4 (25% cotton+75% rice husk), m5 (0% cotton+100% rice husk), m5 (0% cotton+100% rice husk). The second factor is the length of media composting of 5 days (m1) and 10 days (m2). The results showed that the media composition of 75% cotton and 25% rice husk with a composting time of 5 days gave an effect on the components of the results of the diameter of the average yield of 3.1 cm and affected the yield of 160 fruits with a total harvest weight of 1.5 kg per plot.